To Compare Serum Procalcitonin And CRP As Markers Of Neonatal Sepsis - Ahmad, Rafiq; Liaquat, Israr; Mumtaz, Nadia; Zulfiqar, Sughra; Muntaha, Sidra tul; Rafique, Nazia (Journal of Rawalpindi Medical College, 2024)
Objective: This study compares serum Procalcitonin (PCT) levels with CRP as predictive markers for neonatal sepsis. Method: It was a Quasi-experimental study performed in the neonatal intensive care unit (NICU) of Holy Family Hospital, Rawalpindi, for six months from July 2021 to January 2022 after the approval of the ethical board. The study included neonates admitted to the neonatal intensive care unit of Holy Family Hospital with a diagnosis of neonatal sepsis. Parents are permitted via written informed consent. A predesigned proforma was used to record clinical examinations, histories, and outcomes, which included hospital stay duration, complications, neonatal discharge, or mortality. Results: Seventy neonates meeting the study's inclusion criteria were enrolled. The average age in the study was 6.44 ± 5.24 days, with 40 (57.1%) males and 30 (42.9%) females. The CRP test demonstrated a sensitivity of 85.42%, specificity of 81.82%, positive predictive value (PPV) of 91.11%, negative predictive value (NPV) of 72.00%, and diagnostic accuracy of 84.29% in predicting neonatal sepsis. The PCT test displayed sensitivity, specificity, PPV, NPV, and diagnostic accuracy of 87.76%, 90.48%, 95.56%, 76.00%, and 88.57%, respectively. Conclusion: This study underscores Procalcitonin as a superior and early predictor compared to CRP in forecasting neonatal sepsis. Procalcitonin emerges as a particular marker for bacterial infections when contrasted with other inflammation indicators such as CRP, white blood cells, or lactate. Notably, Procalcitonin levels remain unaffected in viral or atypical bacterial infections. Keywords: Serum, Predictor, Neonatal, Sepsis.